Magnetic Field-Enhanced Oxygen Evolution in YMn1–x Cr x O3 (x = 0, 0.05, and 0.1) Perovskite Oxides - Sharma, Parul Kumar; Pramanik, Monidipa; Limaye, Mukta V.; Singh, Shashi Bhushan (Journal of physical chemistry. C, 2023)
The oxygen evolution reaction (OER) plays a key role in various energy applications, and perovskite oxides have received significant interest in recent years as potential catalysts for the OER. Furthermore, magnetic field-enhanced electrocatalysis has emerged recently as a promising way to boost catalytic efficiency in magnetic materials. In the present work, YMnCrO3 perovskite oxide nanostructures were synthesized, and their magnetic properties are altered by Cr doping in YMn1–x Cr x O3 (x = 0, 0.05, and 0.1). The magnetic hysteresis loop confirms the enhanced ferromagnetic exchange interaction with increasing Cr doping concentration. The highest ferromagnetic signal is observed in YMn1–x Cr x O3 (x = 0.1). More interestingly, the OER activities are significantly improved after doping of Cr in YMnO3. The improved OER activity under an applied magnetic field is related to the increase in the ferromagnetic exchange interaction after Cr doping.